The Influence of Brand Image, Price and E-Service Quality on the Purchase Decision of Glad2Glow Products among Students of the Faculty of Psychology, Universitas Prima Indonesia - Hana Syahrani Kaban; Jarungjung Hutagaol; Clarysa Wayn; Lili Lili; Nirwana Br Bangun (SEAN Institute, 2026)
This study aims to analyze the influence of brand image, price, and e-service quality on the purchasing decision of Glad2Glow products among students of the Faculty of Psychology, Universitas Prima Indonesia. The method used is quantitative and descriptive and explanatory in nature, with a sample of 63 respondents determined using the Slovin formula. Data analysis techniques include classical assumption tests, multiple linear regression, t-tests, and F-tests. The results of the study indicate that, partially, brand image has a positive and significant effect on purchasing decisions with a significance value of 0.027 (< 0.05), while price and e-service quality do not have a significant effect, partially, with significance values ​​​​of 0.165 and 0.517 (> 0.05). Simultaneously, the three variables have a significant effect on purchasing decisions, with a calculated F value of 17.088 and a significance level of 0.000 < 0.05. This study concludes that brand image is a dominant factor that influences the purchasing decision of Glad2Glow products. The managerial implication of this study is that companies should focus on strengthening brand image through marketing campaigns that emphasize product excellence. Although the price and quality of e-services do not have a direct significant impact, companies still need to pay attention to these aspects to improve customer experience and create long-term loyalty.